Cultural Exchange among Indigenous Turkish Cypriot Students and Educational Tourists at the Eastern Mediterranean University, Famagusta, North Cyprus - Chukwumah, Henry Ekene (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2018)
This research studies the nature of cultural exchange between indigenous Turkish/Cypriot and Nigerian students studying at the Eastern Mediterranean University in Turkish Republic of Northern Cyrus (TRNC) in the city of Famagusta. The study used qualitative approach in order to develop an in-depth understanding of the issue. In order to collect data, semi-structured interviews were conducted both with the Turkish Cypriot students and Nigerian Students. Interviews conducted supplied valuable data about the nature and types of friendships, and the impacts of these experiences regarding the Turkish Cypriot and Nigerian students. The results showed that both the Nigerian and the Turkish Cypriot students welcomed each other and were ready to exchange and learn from their cultural differences which aided a strong relationship between both groups. Keywords: North Cyprus, educational tourism, cultural exchange, acculturation.

ÖZ: Bu araştırma Kuzey Kıbrıs Türk Cumhuriyeti’nin Mağusa şehrinde bulunan Doğu Akdeniz Universitesi’nin Nijeryalı ve yerli Kıbrıslı Türk öğrenciler arasındaki kültür alışverişinin türünü incelemektedir. Bu araştırmada konu hakkında geniş kapsamlı bir anlayışın oluşması için nicel analiz kullanıldı. Veri toplamak için Nijeryalı ve Kıbrıslı Türk öğrencilerle yarı yapılandırılmış görüşmeler gerçekleştirildi. Bu görüşmeler sayesinde arkadaşlık türü ve deneyimlerin Nijeryalı ve Kıbrıslı Türk öğrencilerlin üstündeki etkileri hakkında önemli bilgiler edinildi. Sonuçlar Nijeryalı ve Kıbrıslı Türk öğrencilerin birbirlerini içtenlikle karşıladığını ve kültür alışverişi gerçekleştirip kültürel farklılıklarından ders çıkarmaya hazır olduğunu gösterdi. Bu ise iki grup arasında güçlü bir ilişkinin kurulmasına yardımcı oldu. Anahtar kelimeler: Kuzey Kıbrıs, eğitim turizmi, kültür alışverişi, kültürel etkileşim
Master of Science in Tourism Management. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Tourism, 2018. Supervisor: Assist. Prof. Dr. İlkay Yorgancı Maloney.
Keywords: Tourism; Tourism--Cyprus, North; Students--Travel; Foreign study--Tourism; North Cyprus; educational tourism; cultural exchange; acculturation